Collective Effort and Its Impact on Educational Guidance and Facing Contemporary Challenges - Al-Douri, Asst. Dr. Iman Musa Al-Douri; Al-Qathami, Prof. Lateefa Al-Qathami (Sulaimani Journal for Humanities, 2026)
The term collectiveijtihad is one of the contemporary concepts produced by increasing scientific development, and the validity of Sharia for different times is dependent on ijtihad concerning the new issues that arise for humans. However, dealing with it on an individual basis may lead to adverse results due to the absence of an absolute mujtahid in our current time. This results in multiple individual ijtihads and the emergence of partisanship to opinions, which can lead us into the condemned disagreements that divide the nation instead of uniting it.To tackle this situation produced by our current reality, it has become necessary for religious specializations to highlight the importance of collective ijtihad and to activate it. Thus, this research attempts to shed light on this type of ijtihad in the field of education.
Keywords: collective effort; educational guidance; contemporary challenges